(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
This article is devoted to the study of the peculiarities of the influence of the COVID-19 stamp on a person, organized by the world’s leading countries, both locally and jointly, within the framework of international programs. Researchers note that the new form of the virus, even with complex treatment, is still capable of causing the so-called “post-Covid” syndrome, characterized by a weakened immune system and a decrease in hemoglobin.